2022
DOI: 10.3390/cancers14184437
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review to Assess Adherence to and Clinical Outcomes of Wearable Devices in the Cancer Population

Abstract: The use of wearable devices (WDs) in healthcare monitoring and management has attracted increasing attention. A major problem is patients’ adherence and acceptance of WDs given that they are already experiencing a disease burden and treatment side effects. This scoping review explored the use of wrist-worn devices in the cancer population, with a special focus on adherence and clinical outcomes. Relevant articles focusing on the use of WDs in cancer care management were retrieved from PubMed, Scopus, and Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The results of our current study are in line with our previous related study results, including two prospective observational studies [ 28 , 29 ] and a scoping review [ 44 ]. One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ]. Additionally, in the third study, wearable devices reported greater angle and spin movements as early as within the first 48 h of observation in the cancer patients who were still alive after discharge from the hospice inpatient unit [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our current study are in line with our previous related study results, including two prospective observational studies [ 28 , 29 ] and a scoping review [ 44 ]. One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ]. Additionally, in the third study, wearable devices reported greater angle and spin movements as early as within the first 48 h of observation in the cancer patients who were still alive after discharge from the hospice inpatient unit [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Eight indicated a positive correlation between the PROs and wearable outcomes [20]. As shown in our previous review, they also found that definitions of the outcome measures and adherence varied across the studies [10,20]. These and other studies [30,31] indicate that there might be a benefit from using wearables in oncology, but also that larger clinical studies confirming this are required.…”
Section: Discussionmentioning
confidence: 60%
“…A recent scoping review by Huang et al showed that out of 38 studies, both during and after cancer treatment and in mixed diagnosis groups, only 10 compared PROs with clinical outcomes. Eight indicated a positive correlation between the PROs and wearable outcomes [20]. As shown in our previous review, they also found that definitions of the outcome measures and adherence varied across the studies [10,20].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Fueled partly by the COVID-19 pandemic and growing need for remote and virtual care, the number of studies of technology-supported health interventions in cancer-including studies on wearables in cancer care-has increased dramatically in the past 3 to 5 years. 1,2 These studies underscore the potential offered by wearable devices across the landscape of cancer care delivery. Wearable devices may be used to support a range of activities including real-time monitoring of patient data, such as heart rate, blood pressure, or sleep quality, as well as allowing patients to directly report symptoms and mood using the wearable device.…”
mentioning
confidence: 94%